2017
DOI: 10.1002/2016ja023792
|View full text |Cite
|
Sign up to set email alerts
|

An isolated, bright cusp aurora at Saturn

Abstract: Saturn's dayside aurora displays a number of morphological features poleward of the main emission region. We present an unusual morphology captured by the Hubble Space Telescope on 14 June 2014 (day 165), where for 2 h, Saturn's FUV aurora faded almost entirely, with the exception of a distinct emission spot at high latitude. The spot remained fixed in local time between 10 and 15 LT and moved poleward to a minimum colatitude of ~4°. It was bright and persistent, displaying intensities of up to 49 kR over a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 86 publications
(176 reference statements)
1
15
0
Order By: Relevance
“…The systematic fitting of circles was limited to those images displaying clear equatorward 10.1029/2018JA025426 Journal of Geophysical Research: Space Physics emission boundaries (see section 4.2) in both the dawn and dusk sectors to constrain the fit; however, during the 2014 campaign, only 26 images were found to be suitable. The auroral oval morphology was very mixed, including periods during which the dawn arc disappeared completely (Kinrade et al, 2017). We found no statistical oscillation of the oval position using these images, but the oval (when present) was offset by a mean~3°toward a LT of~02 LT, consistent with the offset reported by Carbary (2012) and Nichols et al (2016).…”
Section: A1 Rotational Modulation Of Auroral Positionsupporting
confidence: 83%
See 1 more Smart Citation
“…The systematic fitting of circles was limited to those images displaying clear equatorward 10.1029/2018JA025426 Journal of Geophysical Research: Space Physics emission boundaries (see section 4.2) in both the dawn and dusk sectors to constrain the fit; however, during the 2014 campaign, only 26 images were found to be suitable. The auroral oval morphology was very mixed, including periods during which the dawn arc disappeared completely (Kinrade et al, 2017). We found no statistical oscillation of the oval position using these images, but the oval (when present) was offset by a mean~3°toward a LT of~02 LT, consistent with the offset reported by Carbary (2012) and Nichols et al (2016).…”
Section: A1 Rotational Modulation Of Auroral Positionsupporting
confidence: 83%
“…Nichols et al (2016) also observed this pre-noon, LT boundary in HST images from 2011 to 2013, citing the presence of poleward auroral forms around noon to be the probable cause. Poleward forms around noon were also present during this 2014 campaign (Kinrade et al, 2017) and were identified as signatures of dayside reconnection processes. Auroral features poleward of the dayside main emission have been previously linked with cusp emission and bursty reconnection during periods of magnetospheric compression by the solar wind (e.g., Badman et al, 2013;Gérard et al, 2005;Meredith et al, 2015;Radioti et al, 2011), although reconnection signatures in the dayside aurora have also been observed during quiet solar wind conditions and in absence of any other main emission morphology (Kinrade et al, 2017).…”
Section: Boundary Locationsmentioning
confidence: 82%
“…These images were acquired by the HST Space Telescope Imaging Spectrograph (STIS), with the STIS FUV multianode microchannel array using the F25SrF2 long‐pass filter with an exposure time of 840 s. This filter is a band‐pass filter letting 125‐ to 190‐nm wavelengths pass while blocking the H Lyman‐ α emission line at 121 nm. All exposures were background‐subtracted and projected on a planetocentric polar grid (e.g., Clarke et al, ; Kinrade et al, ). This day clearly featured an exceptionally quiet aurora in the northern hemisphere, with none of the images including any dawn emission.…”
Section: Resultsmentioning
confidence: 99%
“…impinging on Jupiter's magnetosphere. This model is used extensively by the outer planets magnetosphere community [11][12][13] in the absence of in-situ measurements of the solar-wind conditions.…”
Section: Methodsmentioning
confidence: 99%